A comparative requirement of space design: green and open space analysis. (21st April 2020) - Ahmad, Puziah; Hashim, Muhammad Shariffullah; Misni, Alamah; Kamaruddin, Siti Mazwin
Planning guideline is a document that governs the design process of our physical environment. It is important in ensuring urban spatial development to oversee whether that is healthy, safe, attractive, and economically viable. This study focused on studying a few sets of planning guidelines, namely for Selangor, Melaka, and Johor States in Malaysia. To have a good outcome, this study compared and analysed the open and green space requirements on the six elements for land use development. An assessment of the guidelines was done using several variables, such as: 1) the amount of open and green space required; 2) vegetation characteristic; 3) green space distribution; 4) configuration. The study findings by the content analysis and ordinal scale assessment suggested that the existing planning guidelines have not been specific on the provision and design aspect for the open and green space. This study suggests some feasible motivations in planning for the enriched Open Green Space Guidelines .